Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer: x = 0 ; y = -7
Step-by-step explanation:
Given equation:
1) 3x + 8y = -56
2) 2x - y = 7
Subtract 2x on both sides of 2) equation to isolate y-value
2x - y - 2x = 7 -2x
-y = 7 - 2x
Divide -1 on both sides of 2) equation
-y / -1 = (7 - 2x) / -1
y = 2x - 7
Current system
1) 3x + 8y = -56
2) y = 2x - 7
Substitute 2) equation into the y-value of 1) equation
3x + 8 (2x - 7) = -56
Simplify by distributive property
3x + 8 × 2x - 8 × 7 = -56
3x + 16x - 56 = -56
Combine like terms
19x - 56 = -56
Add 56 on both sides
19x - 56 + 56 = -56 + 56
19x = 0
Divide 19 on both sides
19x / 19 = 0 / 19
[tex]\Large\boxed{x=0}[/tex]
Substitute the x-value into one of the equations to find the y-value
2x - y = 7
2 (0) - y = 7
0 - y = 7
-y = 7
[tex]\Large\boxed{y=-7}[/tex]
Hope this helps!! :)
Please let me know if you have any questions
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.